Dissertation Experiences of Recent Doctoral Graduates in Accounting. - Parker, James E.; Ford, Allen (The Accounting Review, 1972)
In this article the authors solicited responses of questions relating to dissertation experiences of individuals who were awarded a doctoral degree with a major or emphasis in accounting during the period of September 1, 1965 to August 31, 1970. Questionnaires were distributed to 397 Ph.D. or DBA recipients from forty-four universities of which 297 (75%) of the questionnaires were returned. The first step in compiling the list of doctoral degree recipients to whom questionnaires were mailed was to identify those universities in the United States which offered accounting doctoral programs during the period of September 1, 1965 to August 31, 1970. This was done primarily by combining the lists of such universities reported by authors William F. Crum and Ralph W. Estes. Sixty-one universities were thereby identified as possible grantors of doctoral degrees in accounting. Of the sixty-one universities asked to provide names of degree recipients, forty-five did so, ten replied that they had granted no such degrees, and six failed to reply.